0.25y-3.5=0.15y+1-0.8y

Simple and best practice solution for 0.25y-3.5=0.15y+1-0.8y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.25y-3.5=0.15y+1-0.8y equation:


Simplifying
0.25y + -3.5 = 0.15y + 1 + -0.8y

Reorder the terms:
-3.5 + 0.25y = 0.15y + 1 + -0.8y

Reorder the terms:
-3.5 + 0.25y = 1 + 0.15y + -0.8y

Combine like terms: 0.15y + -0.8y = -0.65y
-3.5 + 0.25y = 1 + -0.65y

Solving
-3.5 + 0.25y = 1 + -0.65y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '0.65y' to each side of the equation.
-3.5 + 0.25y + 0.65y = 1 + -0.65y + 0.65y

Combine like terms: 0.25y + 0.65y = 0.9y
-3.5 + 0.9y = 1 + -0.65y + 0.65y

Combine like terms: -0.65y + 0.65y = 0.00
-3.5 + 0.9y = 1 + 0.00
-3.5 + 0.9y = 1

Add '3.5' to each side of the equation.
-3.5 + 3.5 + 0.9y = 1 + 3.5

Combine like terms: -3.5 + 3.5 = 0.0
0.0 + 0.9y = 1 + 3.5
0.9y = 1 + 3.5

Combine like terms: 1 + 3.5 = 4.5
0.9y = 4.5

Divide each side by '0.9'.
y = 5

Simplifying
y = 5

See similar equations:

| 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 | | 12-5x=-58 | | 7+9x=97 | | A(6a-3)= | | 2+8x=66 | | 6/2X+14 | | 11-4*x+1-3=11+2*4-2x-16 | | 7x-2=103 | | 3.5(c-8)+c=125 | | 6/(2X)=14 |

Equations solver categories